Effect of intracanal dressings on repair and apical bridging of teeth with incomplete root formation - Leonardo, M. R.; Silva, L. A. Bezerra da; Utrilla, L. S.; Leonardo, R. T.; Consolaro, A. (Munksgaard Int Publ Ltd, 1993)
Periapical repair and apical bridging were studied in dog's teeth with incomplete root formation and induced chronic periapical lesions treated with different dressings. A total of 75 root canals from the upper and lower premolars of 4 dogs approximately 6 months of age were chemo-mechanically prepared and filled with the following dressings: antibacterial dressing consisting of a calcium hydroxide+camphorated p-monochlorophenol paste applied for 7 days and followed by monthly renewed calcium hydroxide paste as temporary dressing at 30, 60 and 90 days (Group A); antibacterial dressing consisting of camphorated p-monochlorophenol alone for 7 days, followed by temporary dressing with calcium hydroxide paste renewed at 30, 60 and 90 days (Group B). A control group (Group C) received no dressings. Ninety days after the last calcium hydroxide paste (Groups A, B) and after the last irrigation/aspiration (Group C), the animals were killed, the maxillae and mandibles were removed, and the material submitted to routine histological processing and examination. Both root canal dressings, were of fundamental importance for apical repair and bridging. The apical bridging was predominantly complete in Group A, incomplete in Group B, and absent in Group C. The calcium hydroxide+camphorated p-monochlorophenol combination gave better results than camphorated p-monochlorophenol alone.
Keywords: Anti Infective Agents; Antiinfective agent; Biomedical and dental materials; Calcium hydroxide; Camphor; Camphorated parachlorophenol; Chlorophenol; Animal; Dog; Drug combination; Endodontics; Growth, development and aging; Pathology; Tooth periapical disease; Tooth root; Animal; Anti-Infective Agents; Calcium Hydroxide; Camphor; Chlorophenols; Dogs; Drug Combinations; Periapical Periodontitis; Root Canal Irrigants; Root Canal Obturation; Tooth Root